ANALISIS PENGARUH GAYA HIDUP DAN SIKAP ATAS UANG DENGAN NILAI PRIBADI SEBAGAI MODERASI DI KALANGAN MUDA TERHADAP KEPUTUSAN PEMBELIAN PADA COFFEE SHOP DI KOTA PEKANBARU - Fahrozi, Muhammad; Sulistyowati, Lilis (Jurnal Tepak Manajemen Bisnis, 2015)
The study was conducted at the customers coffee shop in Pekanbaru. The purpose of researchis to analyze the influence of lifestyle and attitude of the money on purchasing decisions with personalvalues as moderation. The study population was young people who visited Pekanbaru coffee shop - acoffee shop in Pekanbaru. Total sample of 150 persons selected by proportional random samplingtechnique. The analytical tool used is moderated stuctural equation modeling (MSEM) using softwareSMARTPLS 2.0 M3.The analysis showed that lifestyle positive and significant impact on purchasing decisions. Then,Lifestyle also positive and significant effect on attitude over money. However, the attitude of money andpersonal values are not shown to influence the purchasing decision. While personal values asmoderation is also no proven effect on purchasing decisions. Recommendations are suggested to theowner of coffee sho is to always follow the trend of the vitality of young people continuously.Furthermore, innovation and continuous improvement to its outlets. Variety of food and drinks on offershould also be considered in accordance with consumer tastesKeywords: Lifestyle, Money Attitudes, Personal Value, Purchasing Decisions, Coffee Shop